The Effect of Vascular Endothelial Growth Factor C and Adipose-Derived Stem Cells on Lymphatic Regeneration in a Rat Vascularized Lymph Node Transfer Model - Jonas, Filip; Kesa, Peter; Paral, Petr; Pankrac, Jan; Kalbacova, Marie Hubalek; Miletin, Jakub; Sukop, Andrej; Molitor, Martin; Staněk, Kryštof; Sefc, Ludek; Mestak, Ondrej (Journal of reconstructive microsurgery, 2023)
BACKGROUND: Lymphedema is a chronic condition characterized by progressive edema with complicated treatment. Recently, new treatment strategies inducing lymphangiogenesis were proposed. The aim of our study was to examine the effect of vascular endothelial growth factor C (VEGF-C) and adipose-derived stem cells (ADSCs) on lymphatic regeneration and drainage re-establishment in vascularized lymph node transfer (VLNT) model using a pedicled vascularized lymph node (VLN) groin flap. METHODS: Female Lewis rats with groin VLN flaps were utilized as a lymphedema model. Group A served as the control. Group B received VEGF-C. Group C received both VEGF-C and ADSCs. Group D received ADSCs only. Lymphatic drainage re-establishment was evaluated by ultrasound-photoacoustic imaging (US-PAI) after indocyanine green (ICG) injection. RESULTS: The fastest regeneration of elevated flaps was observed in Groups B and C in all monitored periods. After the first month, ICG positivity was detected in 14.3% of animals in Group A, 71.43% of animals in Group B (odds ratio [OR] = 15; p = 0.048), and 83.33% in Group C (OR = 30; p = 0.027). On the contrary, the difference between control group and Group D (16.67%; p = 0.905) was statistically insignificant. Administration of VEGF-C, ADSC + VEGF-C, and ADSC led to full flap regeneration after 6 months. The control group had the lowest percentage of ICG positivity at all monitored time points. CONCLUSION: We found that the fastest regeneration occurred with the combination of the VLN flap and VEGF-C. The addition of ADSC had an insignificant effect in our study. Furthermore, we proved the feasibility of PAI as an assessment tool of the lymphatic drainage recovery in a VLNT model.
Keywords: Rats, Inbred Lew; Indocyanine Green; Female; krysa rodu Rattus; zvířata; lymfedém; indokyanová zeleň; Vascular Endothelial Growth Factor C; Stem Cells; Lymph Nodes; lymfatické uzliny; ženské pohlaví; Lymphedema; regenerace; potkani inbrední LEW; Rats; kmenové buňky; Animals; vaskulární endoteliální růstový faktor C; Regeneration